CARDIOVASCULAR COMPLICATIONS AND CARBOHYDRATE METABOLISM IN CORONARY SHUNTING “OFF-PUMP” ACCORDING TO THE REGIMEN OF GLUCOSE LOWERING TREATMENT IN ISCHEMIC HEART DISEASE AND DIABETES - S. Yu. Borodashkina; V. A. Podkamenny; K. V. Protasov (Российский кардиологический журнал)
Aim. To study the shortest term results of coronary bypass (CBG) under “off-pump” circumstances and the condition of carbohydrate metabolism in ischemic disease patients (IHD) with comorbid diabetes 2 type (DM2) under various regimens of perioperation glucose lowering therapy.Material and methods. In the study, the IHD and DM2 patients included, receiving oral glucose lowering drugs (OGLD), with the mean age 57,5 (53-62) y.o., men 99 (78,6%). Before operation the patients were selected to the groups of OGLD (n=61) and insulin (IN) (n=65). In OGLD group the intake of the drugs was continued during perioperation period. In the IN group there was switch to short insulin. The dynamics of carbohydrate metabolism markers in different timeline intervals of postoperation period was studied, and its relation with the glucose lowering regimen. The early postoperation cardiovascular complications (CVC) rate was measured: myocardial infarction, stroke, atrial fibrillation. The carbohydrate metabolism parameters in subgroups of patients was measured, with CVC and without.Results. At baseline there were no differences in carbohydrate metabolism parameters in groups. Loading IN, mean daily glucose levels, its variability and glycemia below the recommended perioperation range (6,1-10,0 mM/L) were lower than in OGLD group. Total number of CVC also predominated in IN group (20,0% vs. 8,2%, p=0,049). Complication subgroups and non-complicated, significantly differed by the baseline glycosilated hemoglobin, mean level of glucose and its daily variability in all timeline intervals studied, as by the prevalence of glucose <6,1 mM/L 0ne day before operation, just before and just after.Conclusion. Patients underwent CBG as off-pump, after switch on short IN, comparing to OGLD patients, have higher mean glycemia level, its variability and number of shifts from recommended range, as higher rate of post-operation CVC.